(untitled) (Academicia Globe: Inderscience Research, 2021)
Inflammation of the tendons of the fingers (tendonitis) is common in horses. These diseases cause significant damage to the life of the animal and its official activities. In addition, the economic costs of treating and caring for sick horses increase. The development of effective methods for the treatment and prevention of equine diseases is of great scientific and practical importance.Foreign [1, 2, 3, 4] and scientists of the department have contributed to the detection, treatment and prevention of joint disease in animals and implemented the results of their research in practice. However, based on the above, treatment and prevention of pelvic and groin inflammations, which are common among horses today, are less common in our region.That is why we have set ourselves the goal of developing effective methods of treating and preventing inflammation in the joints.